Review of Ospreys: The Revival of a Global Raptor , by Alan F. Poole. 2019. - Fields, Lisa; Washburn, Brian E. (DigitalCommons@University of Nebraska - Lincoln, 2020)
For the past three decades, Alan Poole’s (1989) Ospreys: A Natural and Unnatural History has provided a solid foundation for those seeking a primer on the basic biology and ecology of Ospreys (Pandion haliaetus). Poole’s summary of knowledge about Ospreys was written at a time when these amazing birds were recovering from their DDTinduced population crash, but this important book has long been out of print. In the intervening decades, much has been learned regarding Ospreys. In his new book, Ospreys: The Revival of a Global Raptor, Poole guides the reader through a tour of Ospreys’ worldwide distribution and population status followed by an overview of many aspects of Osprey ecology that were previously unknown. Poole’s latest book starts with a brief anecdote about a morning capturing Ospreys in New England (Northeast USA), setting the tone for what to expect in the pages to come, both in terms of the eloquent writing and firstperson- focused content. Chapters 1 and 2 provide the reader with a brief introduction to Ospreys, including such important topics as evolution and identification. Chapter 3 provides a world tour of Osprey populations, progressing from Japan and Australia westward around the globe to the Americas, then circling back to cover Europe. Of particular interest is the discussion of the Caribbean Osprey (P. h. ridgwayi), a nonmigratory subspecies that is relatively unstudied, as Poole is the foremost expert on this fascinating subspecies of Ospreys. The prose is written in a storytelling voice, almost poetic in many places. If you are familiar with Poole’s first book on Ospreys, this will be familiar and comforting. The factual descriptions are interspersed with brief accounts, humorous stories, and passionate descriptions. This sets the book up toward making science, and more specifically what is known about the natural history of Ospreys, accessible to the layperson. There is a strong emphasis throughout the book on the power of citizen science, a contemporary and interesting theme.